Penerapan Nilai-Nilai Pendidikan Akhlak Anak Perspektif Teori Imam Al-Ghazali - fathur rohman (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
In the context of Islamic education, morality occupies an important position, both conceptually and practically. In it there are many normative Islamic contents and examples of good-character leaders. No wonder if Islam is very concerned about morals and places them as an important field of education. It can even be a vital foundation in forming human beings who are noble. So that in time, every human being can occupy his behavior wisely and wisely and be supported by deep Islamic knowledge. Besides that education and morals are integrally possessed of a mandate to prepare humans to be able to understand their position and responsibilities as servants of Allah and the Caliph on earth at the same time.